APPLICATION OF VAR METHODOLOGY IN CASE OF FOREIGN EXCHANGE RISK MANAGEMENT - Račić, Željko; Ercegovac, Dajana (International Journal of Economic Practice and Policy, 2018)
The aim of this paper is to elucidate the importance of monitoring and managing foreign exchange risk by elaborating an example of the application of basic VaR methods. In a detailed overview of the basic procedures that banks use to assess the level of exposure to the risk, readers will be able to learn about basics of practical application of VaR metods. In addition to explaining the application of VaR methodology, the paper analyzes the current exposure of the domestic banking sector to foreign exchange risk. By analyzing these exposures, we concluded that the banking sector efficiently manages foreign exchange risk and that the level of exposure is significantly below the maximum allowed level.